Estudo evolutivo do comportamento hemodinâmico das artérias oftálmicas em puérperas com diagnóstico de pré-eclâmpsia na gestação - Borges, José Hilário Alves (2015)
Objective: To evaluate the hemodynamic behavior of the ophthalmic artery by means of the Doppler ultrasound, in postpartum preeclamptic women. Methods: Observational prospective study with 44 postpartum preeclamptic women (group 1) and 49 postpartum normal women with normal blood pressure and with no previous illnesses known (group 2). All the pregnant women had a Doppler ultrasound exam of the ophthalmic artery in the immediate puerperium, that is, 10 days for the delivery (time 1). Group 1 was then followed prospectively, 26 patients of which returned to the last test in the remote puerperium in 45 days (time 2) and 29 patients returned to the last test in the remote puerperium in 90 days (time 3). The Resistance index (RI), pulsatility index (PI), Peak Systolic velocity (PSV), End Diastolic flow Velocity (EDV), second peak of systolic velocity (P2) and the Peak Ratio (PR) were calculated. The data obtained were expressed in Average and Standard Deviation, by using the Lilliefors Test for Normality. The average of the Doppler indexes in groups 1 and 2 were compared by means of test t of the student. Group 1 was analyzed separately, comparing the three times, using the Test of ANOVA for repetitive measures and Tukey post-hoc range test.Results: Statically meaningful differences in RI, PI, P2, RPV and EDV (p<0,0001, p<0,0001, p<0,0009, p<0,0001, p<0,0028) were found in the immediate puerperium of group 1 in relation to group 2, indicating persistence of hyperperfusion and orbital vasodilatation in the immediate post-partum period in patients who had complicated pregnancies previously due to preeclampsia. In the evolutionary analysis of group 1, comparing the Doppler indexes between the immediate and late puerperium, statistically relevant differences between the rates of RI, P2 and PR (p< 0,01) were observed, showing a raise of RI and reduction of P2 and PR, and also a tendency of normalization of these rates in the late puerperium. When the same indexes were compared (PI, P2 and PR) now in times 2 and 3, the remote and late puerperium respectively, there were no significant differences, indicating stabilization of these indexes since the 45th day of the puerperium. Within 90 days, RI, PI and PR aren’t stabilized yet in relation to the control, even though there is a tendency of these indexes to reach the control. Conclusions:There were persistence of the signs of vasodilatation and hyperperfusion of the orbital territory, represented by the Doppler of the ophthalmic artery in the immediate puerperium of pregnant women who had preeclampsia. A tendency of normalization of the orbital hemodynamic standard in the pregnant women were observed from the late puerperium period on, but there is no complete normalization of the vascular pattern on the remote postpartum.